The role of rental income, real estate and rents for inequality in Germany - Charlotte Bartels; Carsten Schroeder (Forum for a New Economy, 2020)
We quantify the contribution of rental income to pre- and post-government equivalent household income inequality and of housing wealth to net wealth inequality between 2002 and 2017 in Germany by means of a factor decomposition. Further, we differentiate by region types (urban vs. rural, large vs. small municipalities) and federal states. We find that housing wealth, housing ownership and rental income particularly increased in large municipalities and urban areas; that rental income explains an increasing share of income inequality; and that the wealth inequality contribution of primary residence has increased over time, while the contribution of other real estate has decreased. Finally, we find an increasing rent load for the second quintile and the top quintile of the income distribution.
Keywords: C21; D12; D31; 330; inequality; income; consumption; wealth